Apoptotic activity of isoespintanol and semisynthetic derivatives in human polymorphonuclear cells - DADE, Martín; GALEANO, Paula; RÍOS, José-Luis; ROJANO, Benjamín; SCHINELLA, Guillermo (Vitae, 2016)
Background: Inflammation is a complex physiopathologic response to different stimuli. Recently, some pharmacological strategies have been proposed that could be used for resolution of inflammation by enhancing apoptosis of inflammatory cells. Objectives: To study in vitro apoptotic activity of isoespintanol [ISO] and of two semi-synthetic derivatives, bromide isoespintanol [BrI] and demethylated isoespintanol [DMI], in human polymorphonuclear (PMN) cells. Methods: PMN were exposed to the different concentrations of ISO, BrI and DMI for 30 min in phosphate-buffered saline pH 7.4 containing 1 mg/mL glucose, 0.4 mM Mg2+, and 1.20 mM Ca2+. Viability was assessed by dimethylthiazol diphenyl tetrazolium bromide (MTT). To distinguish between the two modes of cell death, apoptosis and necrosis, we examined differences in morphological and biochemical changes of cells stained with annexin V- FITC (An) and/or propidium iodide (PI) using two different assays based on flow cytometry Results: The MTT assay revealed the ability of cells to reduce MTT salt to formazan. In the presence of BrI and DMI a significant concentration-dependent decrease of cell viability was observed. The annexin V- FITC binding assay showed a high proportion of apoptotic cells for those treated with BrI (An+/ PI-: 62.3 ± 8.2% vs. 2.1 ± 0.5% of control, P<0.05). The population of PMN treated with DMI produced the highest percentage (An+/IP+: 43.4 ± 5.2 % vs. 0.4 ± 0.3 % of control, P<0.05) of necrotic cells. Apoptotic nuclei were analyzed by PI staining. The cell population in the sub G0/G1 region represents cells with hypodiploidal DNA, an indicator of apoptosis. When cells were incubated with 50 and 100 μM of BrI, the cell population in the sub G0/G1 region increased, suggesting a dose-dependent increase in the population of apoptotic cells. The presence of the pan-inhibitor of caspases (Z-VAD-fmk) showed a significant reduction in cell population in the sub G0/G1 region, indicating less degradation of DNA. Conclusions: Bromide isoespintanol [BrI] induces an apoptotic process in PMN, mediated –at least in part– by activation of caspases, although this compound may probably act through other caspase-independent mechanisms as well.